GAUGING THE ABILITIES AND DIFFICULTIES OF EMPLOYEES IN WRITING BUSINESS LETTER - C, Emejidio (International Journal of Psychosocial Rehabilitation, 2020)
This study was about the Business writing skills of employees contextualized and tested on Fil-Am Estate Employees, the degree of ability of the Company Employees, the reliability of their Business writing skills, and the congruency of their degree of ability to how much their business writing skills are reliable in accordance to established letter writing system of the BBC. The Quantitative design, specifically analysis and standardized rubric test approach was utilized in the study to analyze the quantitative data through the document analysis from the administered test to 19 Fil-Am Estate Employees. The results revealed that the employees are proficient in writing business letters with regards to the BBC grading system, and prove their competence; reliability and ability in Letter writing. Recommendations were offered to the companies in focusing on training their workforce through workshops to improve the skills of their current and future employees to also improve business transactions and performance.